Impact of incline, sex and level of performance on kinematics during a distance race in classical cross-country skiing - Stöggl, T.; Welde, B.; Supej, M.; Zoppirolli, C.; Rolland, C. G.; Holmberg, H. C.; Pellegrini, B. (Journal of Sports Science & Medicine, 2018)
Here, female and male elite cross-country (XC) skiers were compared on varying terrain during an official 10-km (women) and 15-km (men) Norwegian championship race. On the basis of race performance, 82 skiers were classified as fast (FS) (20 women, 20 men) or slower (SS) (21, 21) skiers. All were video recorded on flat (0°), intermediate (3.5°), uphill (7.1°) and steep uphill (11°) terrain during the race at a distance of 0.8, 1.2, 2.1 and 7.1 km from the start, respectively. All skiers employed exclusively double-poling (DP) on the flat section and, except for the male winner, exclusively diagonal stride (DIA) on the uphill sections. On the intermediate section, more men than women utilized DP and fewer DIA (p = 0.001), with no difference in kick double-poling (DPK). More FS than SS utilized DPK and fewer DIA (p = 0.001), with similar usage of DP. Males skied with faster and longer cycles but lower cycle rate compared with females (p < 0.001), with largest absolute sex differences on flat terrain (p < 0.001) and largest relative differences for cycle velocity and length on intermediate and uphill terrain. External power output rose with increasing incline, being higher for men and FS (p < 0.001). Cycle velocity on flat terrain was the best predictor of mean race velocity for the men, while cycle velocity on steep uphill was the best predictor for the women (both p < 0.001). In conclusion, incline, sex and level of performance influenced cycle characteristics and power output. Greatest absolute sex gap was on flat terrain, whereas the relative difference was greatest on intermediate and steep uphill terrain. We recommend usage of more DP and/or DPK, and less DIA and fewer transitions between techniques on intermediate terrain. Predictors of race performance are sex specific with greatest potential for enhancing performance on flat terrain for men and on steep uphill terrain for women.